Between Word and Body: (Re)Organ-izing the Autobiography in bpNichol’s Organ Music: Parts of an Autobiography - Brubacher, William (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2024)
This paper examines bpNichol’s entanglement of corporeality and textuality through his experimental intervention in the genre of autobiography, titled Organ Music: Parts of an Autobiography. By studying how his autobiography encounters morphologies organizing bodies around the penetration, entry, appropriation and mastery of female bodies, I argue that Nichol's text provides new models for writing the self, embodiment, and sexual difference. The body inscribed in the pages of the text is decentered and abstracted as it comes into contact with and contests the logics of sameness and corporeal impermeability. My work proposes that his text makes legible and resists what Luce Irigaray and Elizabeth Grosz respectively identify as heteropatriarchal “morphologies”—the meanings, vocabularies, and grammars that shape and constitute bodies.